Expression and Association of SCD Gene Polymorphisms and Fatty Acid Compositions in Chicken Cross - Furqon, A.; Gunawan, A.; Ulupi, N.; Suryati, T.; Sumantri, C. (Media Peternakan, 2017)
Stearoyl-CoA desaturase (SCD) is an integral membrane protein of endoplasmic reticulum (ER) that catalyzes the rate limiting step in the monounsaturated fatty acids from saturated fatty acids. Selection for fatty acids traits based on molecular marker assisted selection is needed to increase a value of chicken meat. This study was designed to analyze expression and associations of SCD gene polymorphisms with fatty acid traits in F2 kampung-broiler chicken cross. A total of 62 F2 kampung-broiler chicken cross (29 males and 33 females) were used in this study. Fatty acid traits were measured at 26 weeks of age. Samples were divided into two groups based on fatty acid traits (the highest and the lowest). Primers in exon 2 region were designed from the genomic chicken sequence. The SNP g.37284A>G was detected and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was then used to genotype. The expression of SCD gene was analyzed using quantitative real time PCR (qRT-PCR). The result showed that there were three genotypes (AA, AG, and GG) found in this study. The SCD|AciI polymorphism was significantly associated with palmitoleic acid (C16:1), fatty acids total and saturated fatty acid in 26 weeks old of F2 kampung-broiler chicken cross (P<0.05). The SCD gene was expressed for polyunsaturated fatty acids in liver tissue in two groups of chickens. In conclusion, the SCD gene could be a candidate gene that affects fatty acids traits in F2 kampung-broiler chicken cross.